Draft Annual Plan 2004-2005 Volume-I (Narrative) Government of Rajasthan - Planning Commission (Planning Commission, 2004)
Rajasthan, with a total geographical area of 3,42,239.74 sq. kms., is the largest State in the country. It was formed as a State of the Union of India in March 1949, by the merger of 19 Principalities and two Chiefships, with Ajmer-Merwara being added in 1956 on the recommendations of the States Reorganization Commission. Administratively, Rajasthan is divided today into 6 divisions and 32 districts, which are further sub-divided into 188 sub-divisions, 241 tehsils and 237 development blocks.
Government of Rajasthan, Planning Department